Surgery of the Inferior Vena Cava : A Multidisciplinary Approach - Azoulay, Daniel; Lim, Chetana; Salloum, Chady (Springer International Publishing : Imprint: Springer, 2017)
This book addresses an urgent need, offering an updated, detailed and multidisciplinary review of surgery of the inferior vena cava (IVC). Over the past two decades, tremendous advances have been made in this field and related specialties. Many journals and/or textbooks on different surgical or medical specialties have reported on individual aspects, so it is high time to gather all of them in a single resource. To date, surgery of the IVC remains a major challenge, not only in terms of technical difficulties, but also in terms of perioperative management. The book sheds new light on cutting-edge developments, including: Innovations in imaging; Neoadjuvant and adjuvant treatments for tumors of or involving the IVC; Intraoperative anesthetic management; and Technical and technological advances in surgery. As such, it will be of a great interest to surgeons (cardiac, vascular and digestive) and urologists, as well as radiologists and anesthesiologists.- Resumé vydavatel